A Fully Biomimetic Flexible Sensor Inspired by the Natural Layered Structure of Eggshells for Multimodal Human–Computer Interaction - He, Weiwei; Zhang, Yanzhen; Zhang, Puye; Liu, Yunlong; Wu, Guanyang; Xue, Boce; Hu, Guoqing; Li, Runsheng; Zheng, Chao; Zhang, Dongzhi (Nano-Micro Letters, 2026)
The rapid advancement of naturally microstructure-bioinspired flexible sensors has sparked interest in creating multifunctional systems for human–computer interaction (HCI). However, most existing biomimetic sensors struggle to integrate multiple sensing modes, limiting their practical applications. Herein, this study proposes a design concept for a fully biomimetic sensor. By employing hybrid manufacturing techniques to achieve layer-by-layer biomimicry of the natural layered structure of eggshells, a flexible sensor with multiple sensing modes is developed. The eggshell-inspired multifunctional hybrid flexible sensor (EMHFS) incorporates four functional layers: a triboelectric layer for noncontact sensing, a piezoresistive layer for pressure sensing, and hydrophilic–hydrophobic layers for directional moisture wicking, breathability, and antibacterial properties. The eggshell-inspired structure enables synergistic functionality, allowing seamless switching between contact and noncontact sensing modes. EMHFS demonstrates exceptional performance in multimodal HCI applications, including gesture-controlled robotic hands, wearable unmanned aerial vehicle control systems, and touchless screen password and gesture unlocking, while also exhibiting remarkable sensitivity to weak physiological signals such as breathing and pulse. This fully biomimetic approach offers a novel solution for advanced, flexible, and multifunctional HCI devices. Highlights: 1 Drawing inspiration from natural layered structure of eggshells, a fully biomimetic flexible sensor achieves seamless contact–noncontact sensing switching. 2 Synergistic integration of triboelectric, piezoresistive, and hydrophilic–hydrophobic layers endows the sensor with exceptional sensitivity, long-term durability, antibacterial activity, and directional moisture management. 3 Pioneering multimodal human–computer interaction applications span gesture-controlled robotic hand, wearable unmanned aerial vehicle manipulation, touchless gesture/password unlocking, and high-fidelity monitoring of weak physiological signals.